Transiency of CD-ROM? A reappraisal for the 1990s. - STRATTON, Barbara (1994)
Re-examines the hypothesis that CD-ROM is a transient technology likely to be supplanted. Compares CD-ROM with online information retrieval, and suggests that the poor currency of CD-ROM may be solved by providing complimentary online and CD-ROM services. Discusses the provision of parallel printing, online and CD-ROM versions, networking issues, and the impact of CD-ROM on printed products. Considers current applications of CD-ROM for enabling electronic libraries and for document and database delivery, particularly over networks.